The changing constitution - Harrison, Kevin (Politics study guides., 2006)
Providing an introduction to the topical subject of constitutional change in Britain, this book considers the historical origins of the constitution but focuses on reforms and their likely impact. It includes chapters on: The Legislature: The House of Commons and the House of Lords; The Executive; Electoral Reform and Referenda; and more.